Transmitted HIV drug resistance in treatment‐naive Romanian patients. Issue 7 (16th April 2013) - Temereanca, Aura; Ene, Luminita; Mehta, Sanjay; Manolescu, Loredana; Duiculescu, Dan; Ruta, Simona
Abstract Transmitted HIV drug resistance (TDR) remains an important concern for individuals unexposed to antiretroviral treatment. Data on the prevalence of TDR, available mainly for HIV‐1 subtype B, are now also emerging for other subtypes. In Romania, a steady predominance of subtype F was reported among both long‐term survivor children and newly infected adults. The pol gene of 61 drug‐naïve patients infected with HIV, diagnosed between 1997 and 2011 was sequenced in order to analyze the prevalence of primary resistance mutations and to correlate these with the infecting genotype. Only 5/61 specimens were classified as infected recently using the BED‐Capture Enzyme Immunoassay. Subtype F1 was prevalent (80.3%), however, other HIV‐1 clades are increasingly identified, especially in the group of subjects infected recently. An HIV transmission cluster, associated to injecting drug use was identified by phylogenetic analysis. The overall prevalence of TDR was 14.75%, mainly associated with NRTI resistance (13.11%), TAMs and M184V being the most common mutations. A declining trend of TDR was recorded from 26.08% in 1997–2004 to 7.89% in 2005–2011. No primary resistance was identified among recent seroconvertors. All HIV‐1 strains had minor mutations in the protease and RT genes, often detected at polymorphic positions. The declining rates of TDR might be related to the high efficacy of HAART and to the increasing number of treated patients with virological success who have a low risk of transmission. The recent increase of HIV‐1 infections which involve other subtypes impose a continuous surveillance of the genetic composition of the epidemic. J. Med. Virol. 85:1139–1147, 2013. © 2013 Wiley Periodicals, Inc.